Can a word paint a thousand pictures? Brand- evoked mental imagery in advertising - Gavilan,Diana (Pontificia Universidad Católica de Chile. Facultad de Comunicaciones, 2021)
Abstract: In this research we have used the logo as stimuli to test the brand-evoked mental imagery effect. According to the Dual Coding Theory, familiar brands facilitate additional pathways -visual and verbal- to retrieve arguments to build mental imagery; therefore, brand stimuli in advertising connects consumer with relevant memories and past experiences. Through an online experiment, applied to a sample of undergraduate students this study provides empirical evidence of the differences in mental imagery evoked by mobile digital advertising due to brand familiarity. The hypothesis posited that a familiar brand will be more likely to increase the ability of an ad to evoke mental image through its three dimensions: vividness, quantity, and elaboration. The individual’s ability to use imagery processing information was controlled. Results show differences in the dimensions of mental imagery due to brand familiarity. Findings suggest that below certain level of brand familiarity, mental imagery of ads may decline. Brand familiarity could enhance advertising information processing and thus the generation of visual mental imagery.